Hero - Stephen, Frears; Andy, Garcia; Geena Davis; Joan Cusack; Kevin J O'Connor; Maury Chaykin; Stephen Tobolowsky; Dustin Hoffman (USA Columbia Pictures Corporation, 1992)
Bernie Laplante is having a rough time. He's divorced, his ex-wife hates him and has custody of their son, the cops are setting a trap for him, then to top it all, he loses a shoe whilst rescuing passengers of a crashed jet. Being a thief who is down on his luck, Bernie takes advantage of the crash, but then someone else claims credit for the rescue.
A not-so-nice man rescues passengers from a crashed airliner, only to see someone else take credit.
Laura Ziskin
Languages: English, Turkish, Chinese
Subtitles: English, Turkish
Keywords: Drama; Comedy